Teknologi Informasi dan Dakwah di Era Digital dan Kecerdasan Buatan - Hasby, M.; Munadi, Fathullah; Hajiannor, Hajiannor (PT. Sharia Journal and Education Center, 2025)
The development of information and communication technology has brought significant changes to various aspects of human life, including the practice of Islamic da‘wah. Technology no longer functions merely as a supporting tool, but has evolved into an infrastructure of civilization that shapes communication patterns, social interactions, and the dissemination of religious values within modern society. This paper aims to examine the utilization of information technology in da‘wah activities and its implications for the transformation of da‘wah methods, media, and strategies in the digital era. The discussion begins with an overview of the basic concept of da‘wah and the development of information technology, followed by an analysis of the use of digital media and social media as contemporary da‘wah platforms. In addition to the opportunities offered—such as wider reach, time efficiency, and easier access to religious information—information technology also presents various challenges. These include limited digital literacy among preachers, shifts in religious authority, and potential negative impacts on moral and ethical values. Therefore, this paper emphasizes the importance of adaptive attitudes, adequate technological competence, teamwork, and media ethics in the implementation of da‘wah. Through the appropriate and responsible use of information technology, Islamic da‘wah is expected to effectively convey the message of amar ma‘ruf nahi munkar in a contextual manner and contribute to the realization of Islam as rahmatan lil ‘alamin. Keywords: da‘wah, information technology,, social digital da‘wah media, modern society.